Deed Legal Ad / ART PT Perkebunan Nusantara IX After The Consolidated PTP XV-XVI (Persero) With PTP XVIII (Persero) - Meilyna Dwijanti; Amin Purnawan (Jurnal Daulat Hukum, 2018)
The purpose of this study was to determine the legality of the deed of AD / ART PT Perkebunan Nusantara IX after the consolidation of PTP XV-XVI (Persero) with PTP XVIII (Persero). This research method using normative legal research. The data used is secondary data that is material that provides an explanation of primary legal materials; in the form of deed of AD / ART PT Perkebunan Nusantara IX. Data were analyzed by descriptive qualitative method. The results showed Deeds AD / ART PT Perkebunan Nusantara IX Post-Consolidation PTP XV-XVI (Persero) With PTP XVIII (Persero), in accordance with the process and the provisions of the legislation in force. In the Deed clearly contain 1) the name and domicile of the Company; 2) the purpose and objectives and business activities of the Company; 3) The period of the founding of the Company; 4) the amount of the authorized, issued and paid-up capital; 5) the number of shares, class of shares if there is a following for each classification number of shares, the rights attached to each share, and the nominal value of each share; 6) the name of position and the number of members of the Board of Directors and Board of Commissioners; 7) determination of the place and manner of implementation of the GMS; 8) procedures for the appointment, replacement, dismissal of members of the Board of Directors and Board of Commissioners; 9) procedures for the use of profits and dividend distribution. replacement, dismissal of members of the Board of Directors and Board of Commissioners; 9) procedures for the use of profits and dividend distribution. replacement, dismissal of members of the Board of Directors and Board of Commissioners; 9) procedures for the use of profits and dividend distribution.Keywords: Legality; Deeds; AD / ART; Limited Liability Company; BUMN.